Values in the Picture Book Four Black Ants by Anja Štefan and Zvonko Čoh: Štiri črne mravljice - Sraka Petek, Barbara (Trideset let literarne nagrade večernica, 2026)
The paper examines values in the picture book Štiri črne mravljice (Four Black Ants) by the Slovenian children's author Anja Štefan and illustrator Zvonko Čoh. The aim of the study is to identify the values present in the text, analyse how they are represented through the actions and relationships of the literary characters, and explore their role in shaping the overall message of the work. The theoretical section presents concepts of values, values in children's literature, and the characteristics of the animal fairy tale. The empirical part is based on a qualitative content analysis of the seven stories included in the collection. The identified values were classified according to Schwartz’s theory of basic values and the European Framework of Ethics and Values (EOEV). The findings reveal the predominance of friendship, empathy, mutual support, curiosity, imagination, creativity, and love. The analysis confirms that the picture book conveys important ethical and social values through anthropomorphic animal characters in a subtle and non-moralising way, encouraging readers to reflect on interpersonal relationships, the world, and the individual’s place within it.